(untitled) (Research, Society and Development, 2022)
The outbreak of a new coronavirus was identified in Wuhan, China in late 2019. SARS-CoV-2, spreads through salivary droplets from a carrier causing a respiratory illness. Its clinical behavior is variable and manifests itself with mild symptoms, moderate or developing a severe respiratory infection. The oral cavity was identified as a gateway for the virus and evaluating its possible role as an aggravating factor in the infectivity and progression of the infection was the objective of this study. A retrospective cohort study was performed with data from 274 medical records of patients with COVID-19. They were collected at the patient’s admission, with seven and fourteen days to analyze the occurrence of oral alterations and relate them to the severity of the infection. In total, 154 patients had oral alterations. The most frequent oral alteration was the presence of ulcerations in the mucosa at the three collection times (T0, T1 and T2). Complementary tests were red blood cells, platelets, leukocytes, bleeding time, TGP, TGO, albumin, creatinine, CRP, urea, d-dimer and leukocyte-lymphocyte ratio. No predictors were observed for the development of oral changes in patients with COVID 19. Changes in the oral mucosa were observed in most of the patients analyzed. An association between diabetic patients and the presence of oral lesions was observed in the evaluated patients, after 7 and 14 days. The study revealed that patients with changes in the oral mucosa had a more severe evolution of COVID-19, including death, indicating that the presence of oral changes may be related to an unfavorable prognosis of the infection.